PELATIHAN PERLINDUNGAN DATA DAN KEAMANAN SIBER UNTUK MASYARAKAT DI LKP MUTIARA INFORMATIKA KABUPATEN ASAHAN - Irianto; Andri Nata; Sumantri (STMIK Royal, 2025)
Abstract: The rapid development of digital technology brings various benefits as well as challenges, one of which is the increasing risk of cyber threats and personal data breaches. The digital community, particularly participants at LKP Mutiara Informatika in Asahan Regency, requires a fundamental understanding and skills in protecting personal data and recognizing cyber threats. This community service program aims to provide educational and practical training on personal data protection and cybersecurity. The implementation methods include material delivery, interactive discussions, and practical simulations using real case studies. This program enhanced participants’ understanding of digital privacy, online fraud, and the use of basic security tools. Participants were also able to identify preventive measures to protect their digital accounts. Through this training, the community is better prepared to face the challenges of the technological era and to serve as agents of cybersecurity literacy, while also emphasizing the importance of synergy between education and technology in building safe and responsible digital awareness. Keywords: personal data; cybersecurity; digital community Abstrak: Perkembangan teknologi digital yang pesat membawa berbagai manfaat sekaligus tantangan, salah satunya adalah meningkatnya risiko terhadap keamanan siber dan kebocoran data pribadi. Masyarakat digital, khususnya peserta di LKP Mutiara Informatika Kabupaten Asahan, membutuhkan pemahaman dan keterampilan dasar dalam melindungi data pribadi serta mengenali ancaman siber. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk memberikan pelatihan yang bersifat edukatif dan aplikatif mengenai perlindungan data pribadi dan keamanan siber. Metode pelaksanaan meliputi penyampaian materi, diskusi interaktif, dan simulasi praktik menggunakan studi kasus nyata. Kegiatan ini meningkatkan pemahaman peserta tentang privasi digital, penipuan online, serta penggunaan perangkat pengaman dasar. Peserta juga mampu mengenali langkah pencegahan untuk melindungi akun digital. Dengan pelatihan ini, masyarakat lebih siap menghadapi tantangan era teknologi dan berperan sebagai agen literasi keamanan siber, sekaligus menegaskan pentingnya sinergi edukasi dan teknologi dalam membangun kesadaran digital yang aman. Kata kunci: data pribadi; keamanan siber; masyarakat digital